2013
DOI: 10.1186/1745-6215-14-7
|View full text |Cite
|
Sign up to set email alerts
|

Practical health co-operation - the impact of a referral template on quality of care and health care co-operation: study protocol for a cluster randomized controlled trial

Abstract: BackgroundThe referral letter plays a key role both in the communication between primary and secondary care, and in the quality of the health care process. Many studies have attempted to evaluate and improve the quality of these referral letters, but few have assessed the impact of their quality on the health care delivered to each patient.MethodsA cluster randomized trial, with the general practitioner office as the unit of randomization, has been designed to evaluate the effect of a referral intervention on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“… 48 Deficient interdisciplinary communication across the continuum of care may explain a part of problems experienced with patient referrals and prioritization along with delayed treatments. 49 …”
Section: Discussionmentioning
confidence: 99%
“… 48 Deficient interdisciplinary communication across the continuum of care may explain a part of problems experienced with patient referrals and prioritization along with delayed treatments. 49 …”
Section: Discussionmentioning
confidence: 99%
“…An additional weakness was the lack of a sound analytical plan proposed in the methods paper 11. To ensure transparency, the analysis presented in this paper is therefore simple and based on single-question assessment.…”
Section: Discussionmentioning
confidence: 99%
“…No correction for clustering was made as the estimated ICC was very low (shown below). Aggregation of scores was postulated in the methods paper,11 but discarded as a main outcome as properties of the questionnaire, with a ‘not applicable’ answering category, are not easily suitable for such an approach. However, to assess the effect of clustering, a sum of scores from the GS-PEQ part of the questionnaire was calculated and a multilevel regression model was built with the GS-PEQ score from the questionnaire as the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested guidelines for the specific content of referral letters within different medical specialties (72)(73)(74)(75) and some have shown a beneficial effect of referral templates/form letters on the quality of referral letters (76)(77)(78)(79)(80). Structured templates have also been effective for improving documentation in other medical records, particularly in reports from examinations/procedures (81)(82)(83)(84).…”
Section: Referral Letter Templatesmentioning
confidence: 99%